Socio-demographic factors affecting attitude towards information and communication technology usage - Abu Hassan, Musa; Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril; D’Silva, Jeffrey Lawrence (Science Publications, 2011)
Problem statement: Rural development through ICT has been the focus of the Malaysian government. ICT is an important tool nowadays and in order to be a developed community, the community especially those in the rural areas must use it wisely. Besides the numerous benefits offered by the ICT, it would be helpful to know whether the rural community especially their leaders which are the Village Development and Security Committee (JKKK) members use ICT or not. Approach: This is a quantitative study and the respondents were selected based on the simple random sampling. A total of 240 JKKK members from four states in Peninsular Malaysia were selected as the respondents. A questionnaire was used to gather the data needed. Results: Results obtained revealed that their attitude towards ICT usage was moderate. Further analyses using Independent t-test and ANOVA have identified that the factor of position held and level of education have significant difference with attitude towards ICT usage. The Pearson Product Moment Correlation performed have confirmed that the factors of period of using a computer in a week, period of using internet in a week and income per month have a positive and significant relationship with attitude towards ICT usage. On the other hand, the factors of period of staying in the Village Vision Movement and age have a negative and significant relationship with attitude towards ICT usage. Conclusion/Recommendation: It is recommended that ICT seminars and courses can be conducted to expose and train the JKKK members to be more competent in using ICT. Increasing the number of ICT centers in the community would provide more opportunity for JKKK members to learn more about ICT. These recommendations should be targeted to JKKK members in the lower management level, lower education, lower income, elderly and members who do not use computer and internet.